Design and implementation of non-circular gears based on target transmission ratio - Song, Weizhen; He, Yong (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
Addressing the complexities inherent in current specific non-circular gear design, including the extensive computational demands involved in solving tooth profile feature points and the lack of a rigorous design and verification process, this study proposes a design method grounded in gear meshing theory. Specifically, the method focuses on achieving the target transmission ratio for non-circular gear. First, the pitch curve equation for the non-circular gear is computed. Secondly, an equal arc length algorithm is proposed to determine the polar diameter rotation angle corresponding to the same arc length per turn, generating a non-circular gear envelope diagram using the equal arc length enveloping method. Subsequently, an edge extraction algorithm is presented to obtain the tooth profile feature data. After obtaining tooth profile feature data, the 3D model of non-circular gears is generated. Then, the gear pair is virtually assembled, and the meshing process is analyzed using a motion simulation method. The results show that the tooth profile meshes well, and the angular velocity curve of the driven wheel is consistent with the target transmission ratio. Finally, the processed non-circular gear was inspected, and the results indicated that the error between the produced non-circular gear and the theoretical tooth profile was within a reasonable range. This confirms the accuracy of the proposed method and provides a rigorous design and verification process for non-circular gears, which is beneficial for further analysis in manufacturing and other tasks. This method not only significantly reduces computation time but also simplifies the process of extracting tooth profile feature points, ensuring extraction accuracy.